The Role of Aryl Hydrocarbon Receptor and Crosstalk with Estrogen Receptor in Response of Breast Cancer Cells to the Novel Antitumor Agents Benzothiazoles and Aminoflavone - Mariana A. Callero; Andrea I. Loaiza-Pérez (International Journal of Breast Cancer)
Many estrogen-receptor- (ER-) expressing breast cancers become refractory to ER-based therapies. New antitumor drugs like aminoflavone (AF) and benzothiazoles (Bzs) have been developed and have exquisite antitumor activity in ER+MCF-7 and T47D cells and in a MCF-7 nude mouse model. ER(−) breast cancer cells like MDA-MB-231 are less susceptible. We previously found in MCF-7 cells that these drugs activate the aryl hydrocarbon receptor (AhR) via translocation to the nucleus, induction of AhR-specific DNA binding activity, and expression of CYP1A1, whose transcription is controlled by the AhR-ARNT transcription factor. CYP1A1 metabolizes AF and Bz to a species which directly or after further metabolism damages DNA. In contrast an AhR-deficient variant of MCF-7 or cells with predominantly nuclear AhR expression, such as MDA-MB 231, are resistant. Thus, these drugs, unlike other neoplastic agents, require AhR-mediated signaling to cause DNA damage. This is a new treatment strategy for breast cancers with intact AhR signaling.